Effect of Chinese herbal compound GAPT on the early brain glucose metabolism of APP/PS1 transgenic mice. (April 2019) - Mana, Lulu; Feng, Huili; Dong, Yunfang; Wang, Yahan; Shi, Jing; Tian, Jinzhou; Wang, Pengwen
A number of studies have shown that early-stage Alzheimer's disease (AD) is associated with abnormal brain glucose metabolism before cognitive decline, which may be the key pathological change of asymptomatic AD. The pathogenesis of AD in traditional Chinese medicine is kidney deficiency and turbid phlegm. Based on this, GAPT (a mixture of herbal extracts) was made to invigorate kidney Yang and eliminate phlegm. Previous studies have shown that GAPT can improve and delay the memory decline, but the specific therapeutic target of AD in an early stage has not been studied. The aim of this study was to investigate the effect of GAPT on glucose metabolism in the early stage of AD. Eighty-eight 3-month-old male APP/PS1 transgenic mice were randomly divided into model group; donepezil group; and low, middle and high GAPT dosage groups. Twelve 3-month-old C57BL/6J mice were used as a control group. The Morris water maze test and the Step-Down Passive-Avoidance test were used to evaluate learning and memory ability. Cerebral extraction and the accumulation of glucose were scanned with a micro-positron-emission tomography (PET) imaging system. Immunohistochemistry, western blot analysis and polymerase chain reaction (PCR) were used to detect the expression of the PI3K/AKT-mTOR signalling pathway–related proteins and messenger RNAs (mRNAs) in hippocampus of APP/PS1 transgenic mice after 3 months of drug administration. GAPT can shorten the escape latency and error numbers compared to the model group. In micro-PET imaging analysis, GAPT can increase the glucose uptake average rate in the frontal lobe, temporal lobe, parietal lobe and hippocampus. The immunohistochemistry, western blot analysis and PCR results indicated that GAPT can increase the expression of PI3K, AKT, GLUT1 and GLUT3 in the hippocampus of APP/PS1 transgenic mice. In summary, GAPT can improve brain glucose metabolism damage in APP/PS1 transgenic mice, mainly by increasing brain glucose uptake, increasing glucose transport and improving the insulin signalling pathway.